Miriam Ben-Shalom Papers, 1971-1999: Text Corpus of AV Materials - (:unkn) unknown (My University, 2021)
Miriam Ben-Shalom was the first gay or lesbian member of the United States military service to be reinstated after being discharged for her sexual orientation. The collection documents Ben-Shalom's legal battles with the military, as well as the general topic of homosexuals and the military. Other materials pertain to the gay and lesbian veterans movement, feminism, and related social justice issues. This text corpus was derived from AV materials that are part of the collection. The full finding aid for the collection can be found here: http://digital.library.wisc.edu/1711.dl/wiarchives.uw-mil-uwmmss0237